2002
DOI: 10.1523/jneurosci.22-18-07931.2002
|View full text |Cite
|
Sign up to set email alerts
|

Impaired D2 Dopamine Receptor Function in Mice Lacking Type 5 Adenylyl Cyclase

Abstract: Dopamine receptor subtypes D1 and D2, and many other seven-transmembrane receptors including adenosine receptor A2A, are colocalized in striatum of brain. These receptors stimulate or inhibit adenylyl cyclases (ACs) to produce distinct physiological and pharmacological responses and interact with each other synergistically or antagonistically at various levels. The identity of the AC isoform that is coupled to each of these receptors, however, remains unknown. To investigate the in vivo role of the type 5 aden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
199
1

Year Published

2003
2003
2015
2015

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 147 publications
(209 citation statements)
references
References 46 publications
9
199
1
Order By: Relevance
“…In any case, the main isoform of adenylyl cyclase in the striatum is AC5, and co-stimulation of G s -and G i -coupled receptors shows antagonistic interactions at the AC5 level (Chern, 2000;Defer et al, 2000). In fact, D 2 receptor stimulation has been shown to counteract cAMP accumulation induced by A 2A receptor stimulation in membrane preparations from mouse striatum (Lee et al, 2002).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In any case, the main isoform of adenylyl cyclase in the striatum is AC5, and co-stimulation of G s -and G i -coupled receptors shows antagonistic interactions at the AC5 level (Chern, 2000;Defer et al, 2000). In fact, D 2 receptor stimulation has been shown to counteract cAMP accumulation induced by A 2A receptor stimulation in membrane preparations from mouse striatum (Lee et al, 2002).…”
Section: Discussionmentioning
confidence: 98%
“…A 2A and D 2 receptors exert reciprocal antagonistic interactions that modulate the function of GABAergic enkephalinergic neurons (Ferré et al, 1993(Ferré et al, , 1997Agnati et al, 2003) and recent studies have demonstrated the ability of A 2A and D 2 receptors to heteromerize Kamiya et al, 2003;Ciruela et al, 2004;Woods and Ferré, 2005). A 2A and D 2 receptors are prototypical G s -and G i -coupled receptors, respectively, which play opposite effects on adenylyl-cyclase (Kull et al, 1999;Hillion et al, 2002;Lee et al, 2002). Stimulation of A 2A receptors can potentially stimulate striatal adenylyl-cyclase, with the consequent activation of the cAMP-PKA signaling pathway and the induction of the expression of different genes, such as c-fos and preproenkephalin (Agnati et al, 2003;Ferré et al, 2003Ferré et al, , 2004.…”
Section: Introductionmentioning
confidence: 99%
“…Most are expressed in brain where they show distinct, although overlapping, expression patterns. The lack of specific inhibitors for these distinct forms of adenylyl cyclase has made it difficult to characterize the role each isoform plays in mediating the functions of opioid receptors.Adenylyl cyclase type 5 (AC5) is unique among these enzymes based on its considerable enrichment within the striatum, with lower levels seen in prefrontal cortex and certain other brain regions (15)(16)(17)(18). This enrichment in striatum is potentially important for opioid action, because , ␦, and opioid receptors are highly expressed in this brain region (8,19), where they are best implicated in regulating opioid reward: Activation of striatal and ␦ opioid receptors is rewarding, whereas activation of receptors opposes reward.…”
mentioning
confidence: 99%
“…This enrichment in striatum is potentially important for opioid action, because , ␦, and opioid receptors are highly expressed in this brain region (8,19), where they are best implicated in regulating opioid reward: Activation of striatal and ␦ opioid receptors is rewarding, whereas activation of receptors opposes reward. Therefore, we investigated the physiological significance of AC5 in mediating the behavioral effects of morphine, as well as opioid receptor-mediated inhibition of adenylyl cyclase in striatum, by using recently developed AC5 Ϫ/Ϫ mice (18). increased these latencies, respectively, to 38.0 and 23.5 s at 52°C, and 27.8 and 17.7 s at 55°C (Fig.…”
mentioning
confidence: 99%
“…Dopamine has been demonstrated to affect brain neural architecture during development (Todd, 1992;Swarzenski et al, 1994;Song et al, 2002). Data described above indicate that brain levels of D5 in rats exposed to 160 ppm D5 were approximately twice as high as corresponding blood levels.…”
Section: Other Human Health Concernsmentioning
confidence: 94%